Perceived barriers to seeking cancer care in the Gaza Strip: a cross-sectional study - Mohamedraed Elshami; Bettina Bottcher; Mohammed Alkhatib; Iyad Ismail; Khitam Abu-Nemer; Mustafa Hana; Ahmed Qandeel; Ahmed Abdelwahed; Hamza Yazji; Hisham Abuamro; Ghadeer Matar; Ahmed Alsahhar; et al. (BMC, 2021)
Abstract Background Several factors might contribute to the delay to get cancer care including poor cancer awareness and having barriers to seeking help. This study described these barriers in Gaza and their association with recalling and recognizing cancer symptoms and risk factors. Methods A cross-sectional study was conducted in Gaza. Adult visitors (≥18 years) to the largest three governmental hospitals and adolescent students (15-17 years) from ten high schools were recruited. A translated-into-Arabic version of the validated Cancer Awareness Measure (CAM) was used to collect data in face-to-face interviews. It described demographic data, barriers to seek cancer care as well as recall and recognition of cancer symptoms and risk factors. Responses were compared between adults and adolescents as well as males and females. Results Of 3033 participants approached, 2886 completed the CAM (response rate= 95.2%). Among them, 1429 (49.5%) were adult (702 females; 49.1%) and 1457 (50.5%) were adolescent (781 females; 53.6%). The mean age± standard deviation (SD) of adult and adolescent participants was 33.7±11.7 years and 16.3±0.8 years, respectively. Emotional barriers were the most common barriers with 'feeling scared' as the most reported barrier (n=1512, 52.4%). Females and adolescents were more likely to report 'feeling scared' as a barrier than males and adults, respectively. Higher recall scores for cancer symptoms were associated with lower likelihood to report 'embarrassment', 'worry about wasting doctor's time' and 'difficulty arranging transport'. This was also seen for recalling risk factors, where 'embarrassment' and all practical barriers showed significant inverse associations with higher scores. In addition, greater recognition scores of cancer risk factors were inversely associated with reporting 'embarrassment' and 'feeling scared'. Conclusions The most commonly perceived barriers to seeking cancer care were 'feeling scared' and 'feeling worried about what the doctor might find', followed by practical and service barriers. Females and adolescents were more likely to report 'fear' as a barrier to seek medical advice. Having a higher recall of cancer symptoms and risk factors was inversely associated with reporting most barriers. To improve patient outcome, early presentation can be facilitated by targeting barriers specific to population groups.